Tracheal Adenocarcinoma in a Cat - Correa, Márcia Düster; Gerardi, Daniel Guimarães; Queiroga, Luciana Branquinho; Driemeier, David; Pereira, Paula Reis; Hammerschmitt, Márcia Elisa; Beck, Carlos Afonso de Castro; Trindade-Gerardi, Anelise Bonilla (Acta Scientiae Veterinariae, 2020)
Background: Primary tracheal adenocarcinoma is a rare neoplasm in cats. The clinical signs often are indicative of upper airway obstruction accompanied with dyspnea, stridor, wheezing, exercise intolerance, and cough. The severity of the clinical signs is related to the size of the mass and consequently, the proportion of the tracheal lumen that is obstructed. The diagnosis is made using thoracic radiography and tracheobronchoscopy by collecting fragments for histopathological analysis and removing the mass. The present study aimed to report the case of a cat with tracheal adenocarcinoma. Case: A 17-year-old Persian female cat presented with clinical signs of dyspnea and progressive weight loss. Emergency therapy was started with bronchodilators, antibiotics, and corticosteroids, but there was no response to treatment. Complementary blood and imaging tests were performed. Thoracic radiography revealed soft tissue opacity overlying the dorsal trachea from the third to the fourth rib, bronchial pattern, and pulmonary hyperinflation. Tracheoscopy showed an irregular intraluminal thoracic trachea mass, occluded by approximately 95% of the airway lumen. The mass was biopsied multiple times with endoscopic cup biopsy forceps, followed by removal of approximately 50% of the mass lesion with an endoscopic wire snare. The patient was in intensive care, and since her clinical condition worsened 48 h after the endoscopic procedure, euthanasia was performed. Necropsy revealed a remanescent mass located in the trachea lumen 8 x 3 mm and a nodule in the right caudal pulmonary lobe with 8 mm of diameter . Histological examination showed epitelian cuboidal neoplastic cells with acinar patterns. Only a few mitosis and moderate anysocitosis were observed. The final diagnosis was primary tracheal adenocarcinoma with pulmonary metastasis. Discussion: The initial oxygen therapy associated with bronchodilators and antibiotics can be explained by the history of asthma. Tracheal tumors in cats are considered to be rare, which makes the diagnosis challenging. The suspicion of tracheal neoplasia was only raised after radiographic examination, but it was not possible to state whether it was intra- or extratracheal. The bronchial pattern reported herein can be observed both in inflammatory diseases such as asthma and bronchitis as well as aging-related diseases in animals. Pulmonary hyperinflation, with a caudal displacement of the diaphragm, is seen in bronchial diseases and in cases of tracheal neoplasms, with the latter justified by the retention of air in the pulmonary lobes. Dehydration and weight loss in the animal are justified by severe dyspnea, which makes it difficult to consume food and water. The tracheoscopy procedure was essential to confirm intraluminal tracheal neoplasia with almost complete lumen obstruction. An attempt was made to remove the neoplasms with polypectomy endoscopic forceps. However, because 95% of the trachea was obstructed, the manipulation led to local edema and bleeding, which promoted complete obstruction of the air passage to the lungs. The obstruction impaired the patient's oxygenation, justifying procedure suspension. The instability and worsening of the clinical picture persisted in the subsequent days, which prevented further intervention, culminating in the animal's euthanasia. Adenocarcinoma, in the present case, was in the advanced stage, evidenced by the presence of pulmonary metastasis. Dyspnea severity was related to neoplasm size, proportion of tracheal lumen obstruction, and presence of pulmonary metastasis. The tumor size associated with the presence of metastasis was a determining factor for the classification of neoplasia in the advanced stage, making more invasive interventions impossible and worsening the patient prognosis.